STUDY OF IMMUNOSUPPRESSIVE PROCESSES AFTER KIDNEY TRANSPLANTATION - Ismoilov Ibodjon Imomjonovich (Journal of new century innovations, 2022)
Abstract: Kidney transplantation is the treatment of choice in patients with end- stage chronic renal failure (CRF). All over the world, there is a constant increase in the number of such patients. More than 370,000 patients receive renal replacement therapy in the United States. In 2002, more than 11 thousand kidney transplants were performed in the countries of the European Union, and in the USA - more than 12 thousand kidney transplants.